Sincalide-Augmented Quantitative Hepatobiliary Scintigraphy (QHBS): Definition of Normal Parameters and Preliminary Relationship Between QHBS and Sphincter of Oddi (SO) Manometry in Patients Suspected of Having SO Dysfunction - Drane, Walter E; Johnson, David A (The Journal of nuclear medicine (1978), 1990)
Sphincter of Oddi (SO) dysfunction presents with vague abdominal pain and/or abnormal liver function tests, and is presumably due to SO stenosis or spasm. Clinical, laboratory, and imaging methods of diagnosis have been less than ideal. Initially, we determined normal quantitative hepatobiliary scintigraphy (QHBS) parameters both pre- and post-sincalide administration. Thirty-one "normals" were analyzed, and post-sincalide common bile duct (CBD) dynamics could be satisfactorily determined in 29 (94%) subjects. Normal values at sincalide-augmented QHBS are reported. Next, 10 patients suspected of having SO dysfunction were studied prospectively using SO manometry and QHBS. The two tests were in agreement in seven cases (4: normal CBD dynamics, 3: abnormal). In one case of advanced SO stenosis, QHBS was abnormal, but SO manometry could not be performed. In the two remaining cases, SO manometry and QHBS gave discordant results. Of greatest importance, no significant correlation existed between the quantitative parameters of these two tests. Sincalide-augmented QHBS is possible and may, in the future, be of value in the diagnosis of SO dysfunction and/or partial CBD obstruction.